2021
DOI: 10.1080/13607863.2021.1910792
|View full text |Cite
|
Sign up to set email alerts
|

Associations between unmet needs for daytime activities and company and scores on the Neuropsychiatric Inventory-Questionnaire in people with dementia: a longitudinal study

Abstract: Objectives: To examine prospectively the association between unmet needs for daytime activities and company and behavioural and psychological symptoms of dementia. Methods: We included 451 people with mild or moderate dementia, from eight European countries, who were assessed three times over 12 months. Unmet needs were measured with the Camberwell Assessment of Need for the Elderly. Three sub-syndromes of the Neuropsychiatric Inventory-Questionnaire were regressed, one-by-one, against unmet needs for daytime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Based on these and prior findings, they concluded that the importance of identifying unmet needs is pivotal in the prevention and treatment of BPSD ( Ferreira et al, 2016 ). A similar study by Michelet et al (2021) of 451 PWD, also using CANE, found unmet needs for daytime activities and company were associated with increased affective and psychotic symptoms. They also suggest that interventions to address unmet needs for daytime activities and company may alleviate BPSD in PWD ( Michelet et al, 2021 ).…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations
“…Based on these and prior findings, they concluded that the importance of identifying unmet needs is pivotal in the prevention and treatment of BPSD ( Ferreira et al, 2016 ). A similar study by Michelet et al (2021) of 451 PWD, also using CANE, found unmet needs for daytime activities and company were associated with increased affective and psychotic symptoms. They also suggest that interventions to address unmet needs for daytime activities and company may alleviate BPSD in PWD ( Michelet et al, 2021 ).…”
Section: Methodsmentioning
confidence: 75%
“…A similar study by Michelet et al (2021) of 451 PWD, also using CANE, found unmet needs for daytime activities and company were associated with increased affective and psychotic symptoms. They also suggest that interventions to address unmet needs for daytime activities and company may alleviate BPSD in PWD ( Michelet et al, 2021 ).…”
Section: Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…However, this approach gives equal weight to different domains of need, making it difficult to identify specific domains that warrant policy intervention. A recent study focused on unmet needs in specific CANE domains, such as daytime activities and company [10]. However, this may not capture the overlapping and interactive aspects of various care needs.…”
Section: Introductionmentioning
confidence: 99%